Demokrasi dan ketimpangan pendapatan di Indonesia - Nurul Bariyah (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2022)
Abstract: The concept of democracy and income inequality has become a topic of study by many economists around the world, both in isolation and in conjunction with other concepts in the field of economics. The fifth principle of Pancasila states